Telemedicine experience between two hospitals from Angola and Spain. (9th December 2020) - Gil-Olivas, Eva; Salvador, Fernando; Moreno, Milagros; Bocanegra, Cristina; Aznar, María Luisa; Filipe, Alberto; Pessela, Agostinho; Mateus, Raquel Mª; Zacarias, Adriano; López, Teresa; Cossio, Yolima; Sánchez-Montalvá, Adrián; et al.
Abstract: Objective: Telemedicine uses information and communication technologies to provide services in the field where the distance is a critical factor. The aim of the present study is to describe the experience of a synchronous telemedicine between two hospitals in Spain and Angola. Methods: This is a retrospective observational study of all synchronous telemedicine sessions conducted between the Hospital Nossa Senhora da Paz in Angola and the Vall d'Hebron University Hospital in Spain from January 2011 to December 2014. Results: Seventy-two cases were discussed in the telemedicine sessions. The average age of patients was 18.02 (SD 13.75) years and mostly women (54.38 percent). Reasons to discuss the cases were 46.47 percent doubts in the diagnosis and therapeutic management, 15.47 percent were purely formative cases, and only 8.45 percent treatment doubt. At the time of presentation, 29 percent of the patients were already diagnosed, 95 percent of whom with infectious disease diagnostic, and from the undiagnosed patients 36 percent presented a febrile syndrome. Conclusion: This study shows the viability of synchronous telemedicine between European and African countries without an excessively sophisticated technology.